INSYA’ MUWAJJAH LEARNING STRATEGY AT MADRASAH ALIYAH SWASTA PONDOK PESANTREN NURUL HAKIM MEDAN TEMBUNG - Nursahfitri, Hayatunnisa (Jurnal Al-Hibru, 2024)
Learning strategy is basically an important sequence in a series of teaching and learning processes. Learning strategies are directly related to the selection of learning activities that are considered effective and efficient in providing learning experiences to achieve basic competencies in learning. One way to improve Insya' Muwajjah is by providing the right strategy for students. This study aims to describe the learning strategy of Insya' Muwajjah at Madrasah Aliyah Swasta Pondok Pesantren Nurul Hakim Medan Tembung. This research uses qualitative research methods with a field study approach. Data collection was obtained through observation, interviews and documentation. The result of this study is the strategy used in learning iNsya' Muwajjah is a language skills strategy which is grouped into five skills, namely reading, writing, speaking, and grammar skills. In addition, there is also a problem, namely the lack of student interest in Insya' teaching for students who have different school backgrounds, namely those who graduated from public schools.